(untitled) - Fabozzi, Frank J. (Hoboken N.J., 2001)
In Bond Portfolio Management, Frank Fabozzi, the leading expert in fixed income securities, explains the latest strategies for maximizing bond portfolio returns. Through in-depth discussions on different types of bonds, valuation principles, and a wide range of strategies, Bond Portfolio Management will prepare you for virtually any bond related event-whether your working on a pension fund or at an insurance company. Key topics include investment objectives of institutional investors, general principles of bond valuation, measuring interest rate risk, and evaluating performance. Bond Portfolio Management is an excellent resource for anyone looking to master one of the world's largest markets, and is a perfect companion to Fabozzi's successful guide-The Handbook of Fixed-Income Securities.
Keywords: Portfolio management,Bonds,Quản lý danh mục đầu tư,Trái phiếu